WIPO IP Facts and Figures 2021 (WIPO Publication, 2021)
IP Facts and Figures 2021 from the World Intellectual Property Organization (WIPO) provides an overview of intellectual property (IP) activity using the latest available year of complete statistics. The figures presented are drawn from WIPO’s more comprehensive World Intellectual Property Indicators 2021. IP Facts and Figures serves as a quick reference guide covering 4 types of industrial property which are patents, utility models, trademarks, and industrial designs. IP Facts and Figures 2021 de la Organización Mundial de la Propiedad Intelectual (OMPI) proporciona una descripción general de la actividad de propiedad intelectual (PI) utilizando el último año disponible de estadísticas completas. Las cifras presentadas se extraen de los Indicadores mundiales de propiedad intelectual 2021 más completos de la OMPI. IP Facts and Figures sirve como una guía de referencia rápida que cubre 4 tipos de propiedad industrial que son patentes, modelos de utilidad, marcas registradas y diseños industriales.